2016
DOI: 10.3389/fpls.2016.01448
|View full text |Cite
|
Sign up to set email alerts
|

Moving through the Stressed Genome: Emerging Regulatory Roles for Transposons in Plant Stress Response

Abstract: The recognition of a positive correlation between organism genome size with its transposable element (TE) content, represents a key discovery of the field of genome biology. Considerable evidence accumulated since then suggests the involvement of TEs in genome structure, evolution and function. The global genome reorganization brought about by transposon activity might play an adaptive/regulatory role in the host response to environmental challenges, reminiscent of McClintock's original ‘Controlling Element’ h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 199 publications
(259 reference statements)
3
123
0
Order By: Relevance
“…There is a garnering support that genome and transcriptome orientation via transposon activity might have a role in adaptation and regulation of host stress response (Negi et al, 2016). Besides, regulation of epigenetic mechanisms has an impact on transcriptional activity of TEs in the pathogen infection (Yu et al, 2013;Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a garnering support that genome and transcriptome orientation via transposon activity might have a role in adaptation and regulation of host stress response (Negi et al, 2016). Besides, regulation of epigenetic mechanisms has an impact on transcriptional activity of TEs in the pathogen infection (Yu et al, 2013;Zhu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They have long been assumed as "silent, "junk" or "selfish" DNA; however, recent studies have revealed that most of these repetitive sequences have potential roles in affecting host gene regulation and genomic rearrangements (Lisch, 2013;Ito et al, 2016). In addition several studies have shown that under abiotic or biotic stress TEs are activated or transcribed (Negi et al, 2016). Infections by viruses are one of the main biotic stress types for plants to cope with.…”
Section: Introductionmentioning
confidence: 99%
“…TEs are genomic elements that must be maintained in a silenced and heterochromatic state in most plant tissues, developmental stages, and growth conditions [24, 25]. The constitutive heterochromatic regions are located at the pericentromeric sites, at telomeres, and in the nucleolus organizing regions [2628].…”
Section: Genome Topographymentioning
confidence: 99%
“…The mechanism, therefore, establishes a heterochromatin-like environment within the euchromatin. Environmental stresses may pose a challenge for the maintenance of this chromatin border, as genes and TEs can mutually influence their expression under certain conditions (Negi et al, 2016). Changes in cytosine DNA methylation patterns due to stress have also been reported .…”
Section: Introductionmentioning
confidence: 99%